2010
DOI: 10.1007/s00251-009-0419-2
|View full text |Cite
|
Sign up to set email alerts
|

MHC class II DRB1 gene polymorphism in the pathogenesis of Maedi–Visna and pulmonary adenocarcinoma viral diseases in sheep

Abstract: Ovine pulmonary adenocarcinoma (OPA) and Maedi-Visna (Maedi) are two chronic respiratory diseases of retroviral origin which occur worldwide. It is known that different host genetic factors influence the outcome of viral infections. To determine if variation in the Mhc-DRB1 gene was associated with progression to these ovine diseases, sheep lungs with and without OPA and Maedi lesions were collected. A sequence-based method was applied and 40 different alleles were detected in the sample analysed. In the allel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 37 publications
0
35
1
1
Order By: Relevance
“…Ovine gene regions including CCR5 and DRB1 were previously associated with OPP provirus levels in candidate gene studies [41], [42], [43]. However, the OvineSNP50 BeadChip marker density and distribution were not sufficient for evaluating whether CCR5 and DRB1 gene regions were associated with OPPV infection in the present study.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Ovine gene regions including CCR5 and DRB1 were previously associated with OPP provirus levels in candidate gene studies [41], [42], [43]. However, the OvineSNP50 BeadChip marker density and distribution were not sufficient for evaluating whether CCR5 and DRB1 gene regions were associated with OPPV infection in the present study.…”
Section: Discussioncontrasting
confidence: 56%
“…Moreover, an infected person receiving transplanted stem cells lacking CCR5 may be cured of HIV [39]. In the cases of VMV and OPPV, reports have suggested that host resistance to lentiviral infection may also occur in sheep [40], [41], [42], [43]. Significant breed effects on seroprevalence have also been observed in comingled flocks of purebred sheep, further indicating possible host genetic restriction [10], [12].…”
Section: Introductionmentioning
confidence: 99%
“…Our previous work analysed the involvement of major histocompatibility complex class I and II loci in OPA and identified several alleles associated with the presence of OPA lesions (Larruskain et al 2010(Larruskain et al , 2012a. This SNPbased work extends the analysis of ovine immunity genes that could influence the pathogenesis of OPA, analysing cytokines, a chemokine receptor, Toll-like receptors (TLRs) and three other innate immunity genes with antiviral activity.…”
Section: Introductionmentioning
confidence: 94%
“…3,45 In the MHC class II Ovar-DRB1 study, 41 DRB1*07012 and DRB1*0403 alleles were significantly associated with ovine progressive pneumonia provirus loads 10-fold and 2.5-fold lower, respectively, in the blood of 405 Columbia, Polypay, and Rambouillet sheep in the United States. Another more recent study, 51 in 165 Laxta sheep of Spain, suggested that DRB1*0353 was significantly associated with lung lesions consistent with VISNA. In the CCR5 study, 80 a homozygous deletion in an octamer transcription element site in the promoter of CCR5 was significantly associated with ovine progressive pneumonia provirus loads in the blood that were 2.5-fold lower.…”
Section: Molecular Diagnostic Tests On the Small Ruminant Hostmentioning
confidence: 99%